Building A Foundation for Tax Compliance in The Time of The COVID-19 Pandemic - Eddy Mayor Putra Sitepu (Magister Administrasi Publik, 2021)
The COVID-19 pandemic has had a significant impact on the economy, including the taxation sector. This tumultuous period for taxpayers and the Government can be a golden opportunity to transform the system and institutional governance to create a firm foundation for increasing tax compliance and by extension, tax revenue. This paper examines strategies that are necessary to face spate of changes and uncertainty caused by the COVID-19 pandemic as well as laying the framework for post COVID-19 reality that is characterized by sustainable tax compliance. The results of this study reached the conclusion that the basic concept of the relationship between the Government and taxpayers as a social contract or fiscal contract should underpin the three phases of the formulation of changes in tax policy. For changes to have long-term and sustainable impact, there is need to strike a balance between the three pillars in tax administration, namely, enforcement, facilitation, and trust.